Identification of maize inbreds for hybridization using agro-morphological traits and SSR markers through clustering and population structure analysis - Sneha S; SathyaSheela K.R.V; Ravikesavan R; Selvakumar T; BabuRajendraPrasad V; Sivakumar S; KumariVinothana N; Deepika V (Molecular Biology Reports, 2026)

FTIR spectroscopy and machine learning for detection of Sudan I dye as a hazardous contaminant in turmeric powder - T. Vignesh; D. Selvakumar; P.Y. Mallikarjun; N.K. Geetha; S. Madhankumar; Mandar Jatkar (Journal of Environmental Chemical Engineering, 2026)

Hybrid microgrid optimization for smart cities using Botox algorithm and motif-based heterogeneous attention network - T. Sathesh Kumar; T. Venkatesan; Selvakumar K (Swarm and Evolutionary Computation, 2026)

Quantitative assessment of sugarcane yellow leaf disease impact on growth, yield, and juice quality in major Indian cultivars - R. Viswanathan; R. Selvakumar; K. Nithya; R. Arun Kumar; Shweta Singh; Chandramani Raj; D. Neelamathi; T. Lakshmipathy; R. Nithyanantham; K. Manivannan; K. Kaverinathan (Physiological and Molecular Plant Pathology, 2026)

Elucidating the mechanisms of anthracene and phenanthrene degradation by the halophile Vreelandella piezotolerant DM1 - Ramanathan Duraimurugan; Selvakumar Santhosh; Shahul Hameed Mohamed Hanifa; T. Nageswara Rao; Jayaraman Narenkumar; Zhen Fang; Sandhanasamy Devanesan; Mohammad Ahmad Wadaan; Aruliah Rajasekar; Rajaram Rajamohan (Extremophiles, 2026)

Temporal Dynamics and Characterization of Sugarcane Parental Pool for Rust Resistance under Tropical Climate - R Selvakumar; T Lakshmi Pathy; Gopalareddy Krishnappa; A Anna Durai; R Viswanathan (Tropical Plant Biology, 2025)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Corrigendum to “Advancing nanoarchitectures of 2D WO3/MXene photoanode for enhanced photoelectrocatalytic oxidation of phenol and arsenic in synthetic wastewater” [Environ. Res. 260 (2024) 119676] - G. Bharath; Selvakumar Palanisamy; T. Sivaranjani; A. Karthigeyan; S. Rajakarthihan; Fawzi Banat (Environmental Research, 2024)

Advancing nanoarchitectures of 2D WO3/MXene photoanode for enhanced photoelectrocatalytic oxidation of phenol and arsenic in synthetic wastewater - Bharath G; Selvakumar Palanisamy; Sivaranjani T; Karthigeyan A; S. Rajakarthihan; Fawzi Banat (Environmental Research, 2024)

Influencing factors and environmental feasibility analysis of agricultural waste preprocessing routes towards biofuel production – A review - Selvakumar Periyasamy; Adane Asefa Adego; P. Senthil Kumar; G.G. Desta; T. Zelalem; V. Karthik; J. Beula Isabel; Mani Jayakumar; Venkatesa Prabhu Sundramurthy; Gayathri Rangasamy (Biomass and Bioenergy, 2024)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Genetic diversity in Groundnut (Arachis hypogaea. L) genotypes varying in maturity duration - R. Sangeetha Vishnuprabha; PL. Viswanathan; S. Manonmani; L. Rajendran; T. Selvakumar (Vegetos, 2022)

Opportunity to restore irrigation tanks in the Cauvery delta by mining and deepening - T. R. Neelakantan; C. R. Suribabu; R. Selvakumar (Environment, Development and Sustainability, 2017)

Mapping of coastal aquifer vulnerable zone in the south west coast of Kanyakumari, South India, using GIS-based DRASTIC model - S. Kaliraj; N. Chandrasekar; T. Simon Peter; S. Selvakumar; N. S. Magesh (Environmental Monitoring and Assessment, 2015)

Evaluation of suitable tropical sugarbeet hybrids with optimum time of sowing - A. Balakrishnan; T. Selvakumar (Sugar Tech, 2009)

Integrated nitrogen management for tropical sugarbeet hybrids - A. Balakrishnan; T. Selvakumar (Sugar Tech, 2008)

In vitro propagation of the medicinal plant Plumbago zeylanica L. Through nodal explants - V. Selvakumar; P. R. Anbudurai; T. Balakumar (In Vitro Cellular & Developmental Biology - Plant, 2001)